The Effect of Curcumin Supplementation on Selected Markers of Delayed Onset Muscle Soreness (DOMS) - Babak Nakhostin-Roohi (Annals of Applied Sport Science, 2016)
Inflammation and pain induced by delayed onset muscle soreness (DOMS) can be induced by eccentric exercise or an unaccustomed activity. The condition can causes problems in exercising and for athletes. The purpose of this study was to assess the effect of 150mg curcumin supplementation immediately after intensive eccentric exercise. Evaluations were made for total antioxidant Capacity (TAC), muscle damage markers, and DOMS induced pain. Ten healthy young males (age, 25.0 ± 1.6 years; height, 178.9 ± 4.1 cm; body mass, 81.1 ± 6.8 kg; fat%, 14.2 ± 2.1) completed a double blind randomized-controlled crossover trial to estimate the effects of oral curcumin supplementation (150mg) and a placebo on squat performance and DOMS following unaccustomed heavy eccentric exercise. Curcumin (CU) or placebo (P) was taken at the prescribed dose immediately after eccentric squat exercises; administrations were separated by a 14-day washout period. Measurements were made at the baseline, immediately, 24, 48, and 72h after exercise comprising: (a) limb pain (1–10 cm visual analogue scale; VAS), (b) total antioxidant capacity (TAC) (c) serum markers of muscle damage and inflammation. Measurements taken after exercise showed significantly reduced levels of pain, creatine kinase (CK), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) in C group compared with group P group (P<0.05). TAC remained significantly high in group C after exercise compared with levels in group P (P<0.05). The findings of this study suggest that a 150mg dose of curcumin may have antioxidant, anti-inflammatory and analgesic effects on DOMS.